Inclusive Education Policy at IAIN Pontianak: An AGIL Framework Analysis - Maimunah, Maimunah; Kurniawan, Syamsul (Pascasarjana IAIN Kudus, 2026)
This study examines the resilience of inclusive education policies at IAIN Pontianak. The analysis is motivated by the discrepancy between normative policy frameworks and their practical implementation in higher education. The study analyzes the adaptation, goal attainment, integration, and maintenance of patterns within institutional inclusive education policies. A descriptive qualitative method was employed through interviews, observations, and document analysis. The findings reveal that IAIN Pontianak has implemented inclusive education policies through regulatory strengthening, disability support services, and academic and non-academic programs. Using the AGIL framework, the study demonstrates that institutional adaptability, clear goals, system integration, and the maintenance of inclusive values support policy resilience. These findings reflect a transformation toward a more humanistic, equitable, and inclusive model of Islamic higher education. The study contributes to the development of inclusive education policies in Islamic higher institutions by emphasizing the importance of resilience in sustaining inclusive practices.